Dermis-fat graft for anophthalmic socket reconstruction: indications and outcomes - Galindo-Ferreiro,Alicia (2018)
ABSTRACT Purpose: To evaluate the outcomes of dermis-fat graft procedure for orbital volume replacement in anophthalmic socket. Methods: A retrospective chart review was performed studying all dermis-fat graft surgeries done at King Khlaed Eye Specialist Hospital in the last 10-year period. Sixty-two anophthalmic socket carriers underwent dermis-fat graft during the study period. Data were collected on characteristics of the patients, postoperative complications, cosmesis, and functional results such as the ability to hold an external prosthesis. Results: Mean age of the patients included in the study was 34.2 ± 9.7 years. There were 38.7% of patients with grade 3 anophthalmic socket, 64.5% of patients had an acquired anophthalmic socket, and dermis-fat graft was performed as a secondary procedure in 61.3% of patients. Postoperative complications included lagophthalmos (22.6%), graft necrosis (17.7%), pyogenic granuloma (12.9%), decreased graft size (12.9%), malpositioned lids (3.2%), and volume deficiency (3.2%). The prosthesis was held in place in 49 patients (79%) preoperatively and in 55 patients (88.7%) postoperatively. Conclusion: Dermis-fat graft is an excellent option for congenital or acquired as well as primary or secondary anophthalmic sockets, with or without contraction. The outcomes are favorable, and complications are rare.